Dynamic DNA methylation in the brain: a new epigenetic mark for experience-dependent plasticity - Tognini, Paola; Napoli, Debora; Pizzorusso, Tommaso (Frontiers in Cellular Neuroscience, 2015)
Experience-dependent plasticity is the ability of brain circuits to undergo molecular, structural and functional changes as a function of neural activity. Neural activity continuously shapes our brain during all the stages of our life, from infancy through adulthood and beyond. Epigenetic modifications of histone proteins and DNA seem to be a leading molecular mechanism to modulate the transcriptional changes underlying the fine-tuning of synaptic connections and circuitry rewiring during activity-dependent plasticity. The recent discovery that cytosine methylation is an epigenetic mark particularly dynamic in brain cells has strongly increased the interest of neuroscientists in understanding the role of covalent modifications of DNA in activity-induced remodelling of neuronal circuits. Here, we provide an overview of the role of DNA methylation and hydroxylmethylation in brain plasticity both during adulthood, with emphasis on learning and memory related processes, and during postnatal development, focusing specifically on experience-dependent plasticity in the visual cortex.